ANALISIS NILAI TAMBAH KOPI LUWAK DI KABUPATEN ACEH TENGAH (KASUS HOME INDUSTRY KAWA GAYO) - Wahyu Isnanda Nasution; Hanipan Iwan Jaya (Universitas Quality, 2023)
This study aims to compare the added value of green bean Luwak Coffee in the Kawa Gayo home industry in Central Aceh Regency with Luwak coffee powder ready for consumption. The research method used is a case study using the Hayami analysis method. The sample is determined purposively (purposive sampling), in which the researcher relies on his judgment when selecting members of the population to participate in the study. The data used in this study are primary data and secondary data. The results of this study indicate that the added value in the Kawa Gayo home industry for Luwak coffee powder is more significant than for Luwak coffee green beans with an added value of IDR 41,675. However this is not followed by the added value ratio of Luwak coffee powder variant which is smaller than the green bean luwak coffe on value added ratio of 30.96%. The business scale of the supporting costs that still exist using third parties in production is a factor that affects the added value of processing Luwak coffee grain into Luwak coffee powder in the Kawa Gayo home industry which has yet to be maximized. Home industry obtains higher profit on the Luwak coffee powder variant than the Luwak coffee green bean variant with a profit value of Rp. 37,595. However total of the profits in the home industry from the Luwak coffee green bean variant is higher than the Luwak coffee powder variant with Rp. 1,400,250 profit value. The demand for a variant greatly affects the total profit of Kawa Gayo home industry.